Perspectives on ADHD in children and adolescents as a social construct amidst rising prevalence of diagnosis and medication use - Banaschewski, Tobias; Häge, Alexander; Hohmann, Sarah; Mechler, Konstantin (Frontiers in Psychiatry, 2024)
The diagnosis of attention-deficit hyperactivity disorder (ADHD) is based on the presence of pervasive, persistent symptoms of inattention and/or hyperactivity/impulsivity typically emerging early in life and resulting in significant functional impairment. In contrast to a worldwide epidemiological prevalence of approximately 5% in children and 2-3% in adults, there are significant variations in the prevalence of administrative ADHD diagnoses and medication use. We assert that in order to explore the underlying dynamics of this phenomenon, a thorough understanding of the construct ADHD is necessary. We contend that ADHD is not a natural entity that unfolds within an individual and can be understood independent from societal and environmental factors, but rather that ADHD as a diagnosis can better be conceptualized as a valid and pragmatically useful social construct. Decisions to diagnose and treat ADHD should follow a person-centered approach and be focused on functional impairment within a socially constructed, context-dependent and environmentally contingent model.